1978
DOI: 10.1126/science.202022
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Type C Oncornaviruses: A Model

Abstract: The salient features of this model for oncornavirus assembly are that uncleaved precursor molecules to the internal virus polypeptides possess specific recognition sites both for viral envelope constituents already inserted in the cell membrane and for the viral RNA. After orderly alignment of these components at the budding site, virus maturation proceeds through specific proteolytic cleavage of the precursor components and association of the resultant molecules into the characteristic type C virion substruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(90 citation statements)
references
References 47 publications
7
83
0
Order By: Relevance
“…wt. 80000 to 90000) with the cleavage yielding pl5E and gp70 (Bolognesi et al, 1978;Snyderman & Cianciolo, 1984). Mathes et al (1979) have reported suppression of blastogenesis of feline lymphocytes in vitro to Con A using pl5E.…”
Section: Introductionmentioning
confidence: 99%
“…wt. 80000 to 90000) with the cleavage yielding pl5E and gp70 (Bolognesi et al, 1978;Snyderman & Cianciolo, 1984). Mathes et al (1979) have reported suppression of blastogenesis of feline lymphocytes in vitro to Con A using pl5E.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the positively charged side chain of Arg14 is ideally positioned for electrostatic interactions with the phosphodiester backbone of the nucleic acid. The structural findings provide a rationalization for the general conservation of these hydrophobic and basic residues in CCHC zinc fingers, and are consistent with site-directed mutagenesis results that implicate these residues as direct participants in viral genome recognition.Keywords: human immunodeficiency virus; NMR; nucleocapsid protein; viral genome recognition; zinc finger All retroviruses, including human immunodeficiency virus (HIV), encode a gag precursor polyprotein that functions in the recognition of viral RNA and in the assembly of virus particles (Bolognesi et al, 1978;Dickson et al, 1985). Subsequent to assembly and budding, the gag poly (Berg, 1986) that the arrays function by coordinating zinc (Green & Berg, 1989Roberts et al, 1989;South et al, 1989South et al, , 1990a South et al, ,b, 1991Summers et al, 1990Summers et al, , 1992Fitzgerald & Coleman, 1991;Omichinski et al, 1991).…”
mentioning
confidence: 99%
“…6). It is not known whether the variations in the envelope proteins are due to glycosylation or to structural differences (25).…”
Section: Discussionmentioning
confidence: 99%